New materials and techniques for separation and analysis of clinically important proteins - Kupčík, Rudolf (Univerzita Pardubice, 2019)
This doctoral thesis deals with analysis of peptides and proteins using several analytical methods, mainly chromatography and mass spectrometry with following bioinformatic data processing. For the purpose of analysis of these important biomolecules, various techniques have been developed mainly for their targeted isolation from complex samples. These techniques also utilize newly introduced materials that bring a broad range of benefits such as high selectivity. Immobilization of various enzymes on selected micro- and nanomaterials is dealt with in another part of this thesis. Such created carriers with immobilized enzymes are subsequently utilized either for protein phosphorylation/dephosphorylation or for digestion of proteins.
Nové materiály a techniky pro separaci a analýzu klinicky významných proteinů
Keywords: analýza proteinů; afinitní chromatografie; hmotnostní spektrometrie; mikro- a nanomateriály; TiO2 nanotrubice; rekombinantní proteiny; modifikace proteinů; protein analysis; affinity chromatography; mass spectrometry; micro- and nanomaterials; TiO2 nanotubes; recombinant proteins; protein modifications